"منهج فخر الدين قباوة في علوم القرآن من خلال "التفسير الوافي المفيد لفهم الكتاب المجيد: Fakhr al-Dīn Qabāwah's Approach in the Sciences of the Qur'ān in his Book “al-Tafsīr al-Wāfī al-Mufīd li Fahmi al-Kitāb al-Majīd” - Hocini, Mohamed Amine; GAZEL, SAMIR; TEZCAN, Tuğrul (Online Journal of Research in Islamic Studies, 2022)
ABSTRACT This research aims to uncover the approach of Fakhr al-Dīn Qabāwah in his in his book “al-Tafsīr al-Wāfī al-Mufīd li Fahmi al-Kitāb al-Majīd”. It has also briefly discussed his life and scientific activities.The researchers presented the approach of Qabāwah in the various branches of Qur’ān sciences, such as his method in Mecci and Medanī, the disconnected letters (al-Ḥurūf al-Muqaṭṭa‘a), Qirā’āt and the reasons for revelation (Asbāb al-Nuzūl), the abrogation (Al-Naskh), and the narration of the Israelites (Isrā’īliyyat). The researchers used the inductive approach to follow his approach in the sciences of the Qur’an through his book, “al-Tafsīr al-Wāfī al-Mufīd li Fahmi al-Kitāb al-Majīd”. They also used the analytical approach to study his methods.